PENGARUH PENGGUNAAN MODEL DISCOVERY LEARNING BERBANTUAN MEDIA GAMBAR BERSERI TERHADAP KETERAMPILAN MENULIS TEKS FABEL SISWA KELAS VII SMP NEGERI 2 PADANG - Putrianti, Tika; Emidar, Emidar; Rasyid, Yulianti (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACTÂ This article was written to illustrate the effect of using the serial image media aided discovery learning model to writing skill of fable text of VII students of SMP Negeri 2 Padang. This research data is a score in the skills of writing fable texts before and after using the serial image media aided discovery learning model. This study has three results. First, the skills of writing fable texts before using the serial image media aided discovery learning model in the qualification Enough (C). Second, the skill of writing the text of the fable of the students of grade VII SMP Negeri 2 Padang after using the the serial image media aided discovery learning model is qualified More than Enough (LdC). Third, based on the t test concluded that there is a significant influence on the skill of writing fable text because thitung> ttabel (5,10> 1,70).Â Kata kunci: pengaruh, discovery learning, media gambar berseri, teks fabel